Sustainable and consumer-friendly emerging technologies for application within the meat industry: An overview - Troy, Declan J.; Ojha, Kumari Shikha; Kerry, Joseph P.; Tiwari, Brijesh K. (Meat science, 2016)
New and emerging robust technologies can play an important role in ensuring a more resilient meat value chain and satisfying consumer demands and needs. This paper outlines various novel thermal and non-thermal technologies which have shown potential for meat processing applications. A number of process analytical techniques which have shown potential for rapid, real-time assessment of meat quality are also discussed. The commercial uptake and consumer acceptance of novel technologies in meat processing have been subjects of great interest over the past decade. Consumer focus group studies have shown that consumer expectations and liking for novel technologies, applicable to meat processing applications, vary significantly. This overview also highlights the necessity for meat processors to address consumer risk–benefit perceptions, knowledge and trust in order to be commercially successful in the application of novel technologies within the meat sector. •Application of novel thermal and non-thermal technologies•Novel process analytical techniques for the meat industry•Consumer acceptance of emerging technologies•Sustainability and market uptake